Minimally invasive gastrectomy for cancer: a review - Mirkin, Katelin; Kowalski, Rebecca; Wong, Joyce (Laparoscopic Surgery, 2018)
Although current guidelines do not specifically delineate surgical technique in defining gastrectomy for cancer care, it is widely accepted that open surgical techniques are considered the standard of care. With the advent and increasing experience of minimally invasive techniques and technology, including laparoscopic and robotic platforms, the application of minimally invasive surgery (MIS) techniques has impacted outcomes in gastric cancer care. This review aims to provide an overview of short and long term outcomes as well as utilization of MIS techniques in gastric cancer surgery. Additionally, we address endoscopic techniques as this has become more prevalent, certainly for early stage cancers.